2012
DOI: 10.4028/www.scientific.net/msf.727-728.1848
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Influence of Vortex Finder Geometry on Hydrocyclones Performance

Abstract: The use of hydrocyclones for particles separation is widespread due to advantages such as low cost, simple structure, large capacity and low volume. The shape and size of a hydrocyclone has a decisive effect on the internal flow structure of the continuous phase, and therefore, the separation or classification of the dispersed phase [1]. Therefore, in order to improve the equipments performance, several geometrical changes have been studied in the literature for hydrocyclones of different families [2-13].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The vortex finder and underflow dimensions are also important geometric parameters, and the best values for these variables depend on the role of the equipment (particle classification or thickening) and feed solid concentration. , In addition, some authors have also reported studies on the shape of vortex finder, as it has a significant role in preventing short-circuit and particle misplacing. …”
Section: Introductionmentioning
confidence: 99%
“…The vortex finder and underflow dimensions are also important geometric parameters, and the best values for these variables depend on the role of the equipment (particle classification or thickening) and feed solid concentration. , In addition, some authors have also reported studies on the shape of vortex finder, as it has a significant role in preventing short-circuit and particle misplacing. …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, on the one hand due to the inherent disadvantages (like fish-hook effect or unsatisfactory efficiency [6,7]), on the other hand owing to the new trendies (like the reducing processed particle size [8,9]), the hydrocyclone performance is partly weak, even the device cannot be adopted in some industrial process cases. Therefore, the device performance is tried to be improved by the structural modifications, such as (1) introducing new structures like filtering hydrocyclone [10,11], JK three-product cyclone [12], and two-inlet hydrocyclones [13,14], and (2) changing original structures including the feed pipe [15], the cylindrical section [16], the vortex finder [17], and the conical vessel [16], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, there are changes in the hydrocyclone in order to meet the individual needs of each industrial process. These modifications can be done by creating non-conventional equipment, either by changing the hydrocyclone geometry, or by adding another unit operation in the process of hydrocycloning, or by any other change that is different from the hydrocyclone model initially proposed [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%